1997
DOI: 10.1139/v97-625
|View full text |Cite
|
Sign up to set email alerts
|

Selective aromatic chlorination of activated arenes with sodium chlorite, (salen)manganese(III) complex, and alumina in dichloromethane

Abstract: The reaction of alkyl phenyl ethers with sodium chlorite in dichloromethane in the presence of a (salen)manganese(III) complex and alumina preloaded with a small amount of water afforded monochlorination products with unusually high para selectivities under mild conditions. The NaClO2-based biphasic system can also be successfully used for the regioselective monochlorination of substituted anisoles and polymethoxybenzenes. Keywords: aromatic chlorination, alkyl aryl ethers, sodium chlorite, (salen)manganese(II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Most of the ethers, namely 1, [8] 2a, [9] 2b, [10] 2c, [11] 2d, [12] 2e, [13] 3a, [9] 3b, [14] 3c, [15] and 5d, [16] are described in the literature; 3d, 4c and 5c are new. In nearly all cases, spectral data are not well documented in the literature.…”
Section: Experimental Substancesmentioning
confidence: 99%
“…Most of the ethers, namely 1, [8] 2a, [9] 2b, [10] 2c, [11] 2d, [12] 2e, [13] 3a, [9] 3b, [14] 3c, [15] and 5d, [16] are described in the literature; 3d, 4c and 5c are new. In nearly all cases, spectral data are not well documented in the literature.…”
Section: Experimental Substancesmentioning
confidence: 99%
“…4-Chloro-2-methylanisole (7b). 25 The reaction was performed as described in general procedure A using 2-methylanisole (6b) (124 μL, 1.00 mmol). The reaction mixture was heated to 60 °C for 24 h. Purification by flash column chromatography (petroleum ether/ethyl acetate, 4:1) gave 4-chloro-2-methylanisole (7b) (133 mg, 85%) as a yellow oil.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…: Ph 2 S, AlCl 3 [10] 8.7 : 91.3 -89 b ) 2,3,4,4,5,6-hexachlorocyclohexa-2,5-dienone [11] 5.6 : 94.4 a ) 10 a ) 85 a ) sodium chlorite, cat. : (salene)-mangan(III)-complex [7] -a ) 0 a ) 98 a ) a ) selectivity for the chlorination of anisol; b ) based on chlorination equivalent were formed when lithium bromide was added to the TiCl(OiPr) 3 /TBHP system. To exclude the simultaneous formation of chlorides, we later used TiBr(OiPr) 3 that was prepared by mixing TiBr 4 with three parts of Ti(OiPr) 4 similarly as described for TiCl(OiPr) 3 .…”
Section: Reagentmentioning
confidence: 99%
“…For comparison, the most successful reagents for regioselective para-chlorination are listed in Table 1. With exception of a recent procedure of Hirano et al [7] using sodium chlorite and a manganese(III)-salen complex in the chlorination of anisol some orthochlorination products (3 -8.7%) were always formed in the described procedures.Next, we turned our attention to the bromination of the phenols 1-4. Initially, we observed that bromination products halides 5-11 with the TiX n (OiPr) m /TBHP system (X = Cl or Br).…”
mentioning
confidence: 90%